Temperature-Dependent Phase Transition Studies And Influence Of Hydrogen Bonding Interactions On The Structural And Packing Modes Of Organic Molecules In Single Crystalline State - Quah, Ching Kheng (2011)
In this research, owing to the interests in phase transitions due to hydrogen bonds, fifteen samples with crystal structures and crystal networks that are utilizing the hydrogen bonding were prepared in single crystal form for X-ray structure determination. Temperature-dependent phase transitions studies by single crystal X-ray diffraction is the main experimental method used to study the hydrogen bonding interactions in this research. Fifteen crystal structures were determined and their crystal packing modes were also studied. Only two out of fifteen samples showed phase-transition which were explained macroscopically by Landau theory.